Pain in Persons With Postpolio Syndrome: Frequency, Intensity, and Impact - Stoelb, Brenda L. (2008)
OBJECTIVE: To describe the frequency, intensity, and impact of pain in persons with postpoliomyelitis syndrome (PPS). DESIGN: Retrospective, cross-sectional survey. SETTING: Community-based survey. PARTICIPANTS: Convenience sample of people with PPS. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Overall intensity and duration of pain, pain sites, pain interference, pain treatments, and relief provided by pain treatments. RESULTS: A total of 91% (n=57) of the study participants (N=63) reported pain. The most frequently reported pain sites were the shoulders, lower back, legs, and hips. Participants reported pain intensity to be the greatest in the knees, legs, wrists, lower back, and head. Pain interfered most with sleep and with activities requiring a high level of musculoskeletal involvement. Respondents also reported pain problems that were more severe than those of the general population and than those of a sample of people with multiple sclerosis. Many treatments had been tried previously for pain, but continued use of treatments was reported by relatively few participants at the time of the survey. CONCLUSIONS: The findings indicate that pain is a persistent and common problem in persons with PPS, highlighting the need for effective and accessible pain treatments for this population.